Assessing a Diagnostic Test for Theories of Acid-Base Solutions: a Banjarmasin Study - Tamara Lutfiana Putri; Rizki Nur Analita (EduChemia: Jurnal Kimia dan Pendidikan, 2026)
Misconceptions regarding acid and base solution learning remain a challenge, but the assessment instruments used are still unable to evaluate students’ in-depth understanding. The following study aims to develop a four-tier diagnostic test for acid and base solutions, an assessment instrument in the form of a test based on the Borg and Gall model of research and development (R&D) method. Data were collected from 360 students in Grade 12 Science Classes at three public senior high schools in Banjarmasin, Indonesia. Through a validation process carried out by six validators, consisting of chemistry teachers and lecturers, ten items for a four-tier diagnostic test were identified. Furthermore, all test items were tested and found to meet the validity criteria at a significance level of 0.01 and demonstrated high reliability, with a Cronbach’s alpha value of 0.804. The difficulty level was categorized as medium, while the discrimination index was categorized as fair. This finding indicates that the instrument can be used effectively to assess students’ level of conceptual understanding. Moreover, this four-tier diagnostic test can be applied within the scope of acid-base solution theory learning at Banjarmasin High School.